Hemoparasitismo e razão heterófilo/linfócito no biomonitoramento de aves do Cerrado - Ribeiro, Paulo Vitor Alves (2022)
Organisms that experience stressors and undergo morphophysiological and behavioral changes are called biomonitors. Birds are model organisms for biomonitoring studies because they are sensitive to environmental changes. In this study, the heterophil/lymphocyte ratio (H/L - indicative of chronic stress), prevalence and parasitaemia of hemoparasites were used as biomonitoring tools in Cerrado birds. The objective of this study was to compare the H/L ratio and hemoparasitism of birds between areas with different levels of urbanization and environmental conditions. A total of 1288 birds (41 species) were captured in six Cerrado forest fragments, between 2013-2019, for the production and analysis of blood smears. The forest fragments were classified into rural, peri-urban, and urban, and in each one the levels of noise (anthropic noise) and atmospheric (carbon monoxide) pollutants were measured, and the size of the area occupied by water resources was also calculated in a radius of 1 km². There was a higher H/L ratio in birds captured in urban and peri-urban areas and with high levels of noise and air pollutants, and a lower H/L ratio in individuals from rural areas and with low levels of pollutants. Altogether, 519 (40.2%) individuals were infected with haemosporidian parasites, 516 (40%) with Plasmodium spp. and 13 (1.0%) by Haemoproteus spp. Parasitaemia was not associated with the level of urbanization, but it differed among the six forest fragments, being higher in those where there is a greater amount of water resources. Experimental tests were also carried out with domestic canaries (Serinus canaria). The canaries were divided into two groups; one kept in an urban center (n=20), and another in a rural area far from urbanization (n=20). In both locations, the levels of atmospheric pollutants were measured, carbon monoxide and particulate matter. The experiment lasted 120 days and every 15 days blood collections were made. The H/L ratio was higher in canaries from the urban and more polluted area and increased with time of experiment. Infections by haemosporidian parasites (Plasmodium spp.) were higher in rural canaries, with an average prevalence of 57.1% in rural and 1.11% in urban canaries. Parasitemia was negatively correlated with the H/L ratio in both native birds and canaries, suggesting that individuals may be immunologically active. This study showed that birds that live in urbanized and polluted areas have higher stress indicators (H/L ratio) and that haemosporidian parasites are favored in areas that can offer more resources for vector reproduction and development. These results suggest that the H/L ratio and hemosporid parasites can be used as tools for environmental biomonitoring and as parameters to assess the conditions of birds in degraded environments.